Dielectric properties of BT-BT and BF-BT composites. (10th September 2018) - Balčiūnas, Sergejus; Ivanov, Maksim; Watanabe, Miki; Matsumoto, Ken; Ueno, Shintaro; Fujii, Ichiro; Banys, Jūras; Wada, Satoshi
Abstract: This paper presents dielectric properties of BT-BT and BT-BF composites obtained by solvothermal solidification. We observe lower dielectric permittivity in BT-BT composites than in conventional sintered BT ceramics. The frequency dependence showed two relaxation regions that occur due to domain wall motion and acoustic resonance. Also we observed higher dielectric permittivity for BT-BF system than in conventional BF ceramics which can be attributed to addition of BT or due to epitaxially introduced strain. Lastly, we observed glassy behaviour in BT-BF system.